THE EFFECT OF FINANCIAL COMPENSATION ON EMPLOYEE PERFORMANCE MEDIATED BY WORK SATISFACTION IN DGT REGIONAL OFFICE OF SOUTH SULAWESI, WEST SULAWESI, AND SOUTH-EAST SULAWESI - BL, Muchran (Perpustakaan dan Penerbitan Unismuh Makassar, 2021)
The aim of this study is to examine and analyze the effect of financial compensation on the performance of employees through job satisfaction in DGT Regional office of South Sulawesi, West Suawesi and South-East Sulawesi.The data were collected by a survey method using questionnaire instruments They grouped into into five groups. Of the 1.701 employee population, there were 352 employees who gave responses. The data were then analyzed using the Structural Equation Model (SEM) with the help of the SPSS AMOS application. The results show that financial compensation does not have a significant effect on employees’ performance, but it has a significant indirect effect through job satisfaction.